Ekstrak Daun Ricinus communis L. sebagai Antimikroba Alami: Pengembangan Antimikroba Baru terhadap Mikroba MDR - Nurul Annisa Azmy (Medula, 2020)
The emergence of microbes multidrug-resistant (MDR), caused by overuse of antibiotics, induce a dramatic decrease in the efficacy of antimicrobial drugs. Natural products can be used as exploration and development of new antimicrobials. Plants are a natural source that contains ingredients for traditional medicines. Plants are a source of phytochemical with various bio-structures and effective bioactivity against a number of diseases including bacterial infectious diseases. More than 80% of the world's total population relies on herbal medicines to meet their primary health care needs. The use of plants as alternative medicine is widely used by the community, in addition to being easily available, these medicinal plants rarely have side effects such as synthetic drugs. Extracts from plants are widely used by humans for various purposes including solving human health problems for example, herbal medicines used their antimicrobial properties to treat other diseases due to the activity of secondary metabolites contained in them. One of the herbs that is believed to be antimicrobial, namely Ricinus communis L. Jarak Kepyar or Ricinus communis L. is a plant that easy to grow in the field or in open areas, is resistant to drought and can grow in various soil conditions. Ricinus communis L. leaf extract contains various kinds of phytochemical compounds which play a role in inhibiting bacterial growth. The mechanism of inhibition of bacterial growth occurs through inhibition of the synthesis of microbial cell walls so that microbes will die.